Civil liability of companies for anonymous comments posted on their sites: a criterion of potential consequences of liability - Jurkevičius, Vaidas; Šidlauskienė, Jūratė (Business, Management and Economics Engineering, 2021)
Purpose – The purpose of this study is to investigate a criterion of potential consequences of liability of an Internet portal for unlawful comments of its visitors and set certain general waymarks, which would apply to cases of this kind. Research methodology – The European Court of Human Rights has ruled in four cases (Delfi AS v. Estonia, MTE & Index v. Hungary, Pihl v. Sweden and Tamiz v. the United Kingdom) on whether civil liability can be justified to the website operators for anonymous comments made on their portals that violate the right to privacy. One of the criteria of such evaluation was the possible negative consequences of the civil liability of these entities, but its content and meaning have not been thoroughly studied in the doctrine. Therefore the authors analyse the content of this criterion on the basis of a comparative method. Taking into account the legal context of this study, specific methods of legal interpretation are used in this article (such as, systemic, teleologic, histrorical). Findings – Authors conclude that addressing the civil liability of website operators for damages caused by anonymous comments violating the right to privacy must consider not only the financial, and not only ad hoc, short- and long-term adverse effects of the website operators in general, but the impact of the ruling on the concept of free media and other property and non-material consequences for a democratic society as a whole. Research limitations – This article deals with one criteria for the application of civil liability of website operators for the infringement of an individual’s right to privacy by anonymous comments, that is – the possible negative consequences of the civil liability of these entities. That is the continuation of the authors’ research on the topic of website operator’s liability for unlawful anonymous comments. Practical implications – The research reveals that the consequences of applying the civil liability to the website operator are conditions for assessment of extent of the already existing civil liability; therefore, the criteria of the consequences that arose and / or could arise to website operator are not to be considered as factors justifying the application of civil liability, but rather as factors determining, i.e. extending or limiting, the extent of civil liability. Originality/Value – The vacuum of a consistent concept of assessing the behavior of website operators in response to unlawful comments poses a threat not only to the sustainability of website operators as business or public interest entities, but also to the stability of the legal system as a whole. It is therefore important to disclose the content of elements of assessment of the necessity of restricting the freedom of expression of website operators in a democratic society, which are unregulated and formulated only in the case law of the ECtHR, and which have been applied in national courts for horizontal civil liability claims for anonymous comments. There are no previous research that would focus on these issues.